Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.2320/matertrans.43.2063
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties at Room Temperature to 823 K of Mg-4Y-3RE Alloy

Abstract: This paper describes tensile properties of a peak-aged Mg-4Y-3RE alloy at room temperature to 823 K with 10 −5 -10 −1 s −1 . The Mg alloy exhibited high strength (> 250 MPa) at room temperature to 473 K. However, the strength rapidly decreased at 573 K. It is suggested that a large decrease in strength at 573 K is attributed to grain boundary sliding. Also, elongation increased rapidly at 723-823 K. This is likely to arise from the relatively high strain rate sensitivity of about 0.3 due to the glide-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…8) For the specimen with the grain size of 450 mm, however, such irregularities were not observed and there was no evidence for grain boundary sliding. Mabuchi et al 8) investigated the contribution of grain boundary sliding to total strain at 573 K with 1:7 Â 10 À5 -1:7 Â 10 À1 s À1 for the Mg alloy with the grain size of 60 mm and they revealed that the contribution of grain boundary sliding to total strain is 5-30%, which is much lower than those for superplasticity (¼ 50{80% 17,18) ). Clearly, grain boundary sliding is not the dominant deformation process for the specimen with the grain size of 60 mm.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8) For the specimen with the grain size of 450 mm, however, such irregularities were not observed and there was no evidence for grain boundary sliding. Mabuchi et al 8) investigated the contribution of grain boundary sliding to total strain at 573 K with 1:7 Â 10 À5 -1:7 Â 10 À1 s À1 for the Mg alloy with the grain size of 60 mm and they revealed that the contribution of grain boundary sliding to total strain is 5-30%, which is much lower than those for superplasticity (¼ 50{80% 17,18) ). Clearly, grain boundary sliding is not the dominant deformation process for the specimen with the grain size of 60 mm.…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6] The grain boundary diffusion coefficient is large for Mg, 7) and grain boundary sliding occurs even in a Mg alloy with a relatively large grain size. 8) In addition, twining easily occurs in Mg due to the lack of slip systems. 9) Twining is affected by the grain size.…”
Section: Introductionmentioning
confidence: 99%
“…In reference [59], the authors reported the properties of Mg-4Y-3.2RE at room temperature and reported that ageing improved the strength of the alloy significantly. Su et al [60] reported the properties of peak aged WE43 alloy as shown in Table 16.…”
Section: Mg-re Higher Alloy Systemsmentioning
confidence: 99%
“…Thus, it is suggested that the defect developed in this study is considered to prevent the wave propagating strongly, however, it is difficult to assess by area macroscopically. Magnesium has a high grain-boundary diffusion coefficient 23) and it would induce creep at room temperature. 24) Especially, pure magnesium is considered to be subject to creep due to free from precipitate.…”
Section: Reflection Methodsmentioning
confidence: 99%